Functional evaluation after cortical button fixation for distal biceps ruptures – Is there any difference between manual or non-manual workers? - A. Batista; N. Moura; M. Sarmento; T. Coelho; D. Gomes; R. Ramos; A. Cartucho (Revista Española de Cirugía Ortopédica y Traumatología)
Background: This study aims to compare clinical and functional results after distal biceps tendon repair in manual workers vs. non-manual workers. Methods: This is a retrospective comparative study which refers to 57 cases with distal biceps tendon rupture, divided in manual workers (24 elbows) and non-manual workers (33), that were treated by a single incision with cortical button and interference screw fixation. Included cases have a minimum of 3 months follow-up, post-operative X-ray and signed informed consent for the investigation. Results: Supination and flexion strength was higher in manual workers vs. non-manual workers (p-value = 0.192 and 0.878, respectively). Nine patients showed loss of range of motion, concerning supination and pronation, and this was correlated to worse functional scores. Functional scores tend to be superior in non-manual workers. Ten patients had heterotopic ossification and 20 patients reported lateral antebrachial cutaneous nerve neuropraxia; one had both. Most of them had a full recovery. Conclusion: According to clinical evaluation and post-operative scores, the performed surgical procedure provides good to excellent mid-term functional results. Nevertheless, there were not any differences between manual or non-manual workers. Resumen: Introducción: Este estudio tiene como objetivo comparar los resultados clínicos y funcionales tras de la reparación del tendón distal del bíceps braquial (RTDBB) entre trabajadores manuales y no manuales. Material y Método: Estudio retrospectivo comparativo de 57 casos con rotura del tendón distal del bíceps, divididos en trabajadores manuales (24 codos) y no manuales (33), tratados mediante una única incisión de la piel con botón cortical y fijación con tornillos de interferencia. Los casos incluidos tienen un seguimiento mínimo de 3 meses, radiografía postoperatoria y consentimiento informado firmado para la investigación. Resultados: La fuerza de supinación y flexión fue mayor superior en los trabajadores manuales que en los trabajadores no manuales (valor de p 0,192 y 0,878, respectivamente). Nueve pacientes presentaron pérdida de rango de movimiento, relativo a supinación y pronación, y se han correlacionado con peores puntuaciones funcionales. Las puntuaciones funcionales tienden a ser superiores en los trabajadores no manuales. Diez pacientes han presentado osificación heterotópica y 20 pacientes neuropraxia del nervio cutáneo antebraquial lateral; uno ha tenido ambas. La mayoría se recuperaron por completo. Conclusión: En consecuencia de los resultados clínicos y los funcionales, la RTDBB aporta buenos a excelentes a mediano plazo, sin complicaciones significativas. Aunque no han podido apreciarse diferencias entre trabajadores manuales y no manuales.